Mastitis treatment in Karnataka: Results from a qualitative scoping survey - Hiremath, Arpita; Hoffmann, Vivian; Rao, Manaswini; Shenoy, Ashish (International Food Policy Research Institute, 2025)
Bovine mastitis, inflammation of a cow’s mammary gland, is estimated to cost Indian dairy farmers approximately 1.5 billion US dollars each year through the reduction of milk production and quality (Banal and Gupta, 2009). Milk production may decrease by as much as 17.5% before any noticeable signs of infection are present (Krishnamoorthy et al., 2021), with even larger losses in the case of clinically observable mastitis (Singh and Singh, 1994). Prevalence of sub-clinical mastitis in India has been estimated at 42% and is increasing with warming global temperatures (Krishnamoorthy et al., 2021; Jingar, Mehla, and Singh, 2014).